Rockets' red glare - Webster, William; Lochte, Dick (Sage Mendiluze Series, 2025)
After two wilderness guides are gunned down in a national forest near Wyoming's Wind River Indian Reservation, Tribal Police Deputy Sage Mendiluze is called in to investigate, with his Australian shepherd, Peak, by his side. When more visitors to national parks are murdered, Sage is recruited by Special Agent Maggie Comstock to join the task force tracking the perpetrators.